The impact of The Quality and Safety Education (QSEN) program on the knowledge, skills, and attitudes of junior nurses - Salam AlRatrout; Imad Abu Khader; Mohammed ALBashtawy; Mohammed Asia; Abdullah Alkhawaldeh; Salam Bani Hani (PLoS ONE, 2025)
Background The quality and safety education for nurses (QSEN) competency program represents a valuable initiative in nursing practice and education, equipping nurses with the essential knowledge, attitude, and skills (KAS) required to deliver safe, efficient, and patient-centered care. Purpose This study aims to determine the impact of QSEN competency on the KAS of nurses in Palestine. Method A quasi-experimental pre-test and post-test design with two groups was used utilizing a questionnaire to collect data from 164 Junior nurses in two governmental hospitals within the period of 25th, January to the 10th February 2024. Patricia Benner’s theory suggests that a strong educational foundation and diverse experiences enable nurses to enhance their patient care knowledge and abilities over time. Results The findings indicate that nurses in Palestine can benefit from targeted interventions and QSEN educational programs aimed at improving their patient-centered care competence, as post-test scores show a significant rise over pre-test scores. Junior nurses who participated in the QSEN program experienced a 57% increase in knowledge, a 57% increase in skills, and a 64% increase in attitudes. The intervention significantly improved knowledge (77.02 vs. 49.19, p < 0.001), quality and safety skills (70.16 vs. 44.61, p < 0.001), and attitudes (75.47 vs. 46.16, p < 0.001) among participants post-procedure, indicating a substantial positive impact on these areas, demonstrating the effectiveness of the educational intervention. Conclusion The study demonstrates that an educational intervention improves junior nurses’ KSAs for six QSEN competencies, leading to higher average scores in quality and safety competence subscales, thereby enhancing staff satisfaction, and reducing medical errors, and patient safety.